Development of a Web-Based Geographic Information System for Mapping MSME Locations - Aditya Dwi Ramadhan; Nabila Iskandar; Muhammad Aiman Hakim (Journal of Computer Science and Information Technology, 2026)
The advancement of information technology has encouraged the utilization of web-based Geographic Information Systems (GIS) to support the management and promotion of Micro, Small, and Medium Enterprises (MSMEs). This study aims to develop a web-based GIS capable of mapping MSME locations interactively, informatively, and accessibly. The research method adopts the waterfall software development model, including requirement analysis, system design, implementation, and testing. Data were collected through observation, interviews, and literature review. The system was developed using web technologies such as PHP, Laravel framework, and digital map integration with Leaflet and Mapbox. The results indicate that the system effectively presents spatial and non-spatial MSME information, equipped with search features, category filters, and navigation tools. System testing shows a high success rate and positive user responses. Therefore, this system can improve accessibility of MSME information and support location-based decision-making.